2011
DOI: 10.1111/j.1468-2494.2011.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental and clinical studies of the facial skin tone and pigmentation of Shanghaiese women. Changes induced by age and a cosmetic whitening product

Abstract: The pigmentation patterns of facial skin of 354 healthy Chinese women aged 18-80 years were investigated clinically and instrumentally. Chromasphere(®) was used to acquire pictures from the cheeks of subjects. Facial skin tone was described by L* parameter from the L,a,b system as well as Individual Typology Angle (ITA). Results show that skin tone becomes significantly darker along the life span. Both size of hyper-pigmented spots and their contrast with surrounding skin were found increased with age. As addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 22 publications
6
32
1
Order By: Relevance
“…The selection of the same group of Chinese women in the winters of both 2008 and 2011 allowed us to assess the possible interaction between a 3-year period of skin “aging” and skin tone, to determine more precisely the impact of daily sun protection on skin tone, and to analyze the present findings in light of our previous research 3,4Figures 6–8 indicate a slight but not statistically significant 0.1 unit decrease in L*, a statistically significant increase in b* ( P = 0.049), and a statistically significant 1.0 unit decrease in ITA ( P = 0.04) between the winters of 2008 and 2011.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The selection of the same group of Chinese women in the winters of both 2008 and 2011 allowed us to assess the possible interaction between a 3-year period of skin “aging” and skin tone, to determine more precisely the impact of daily sun protection on skin tone, and to analyze the present findings in light of our previous research 3,4Figures 6–8 indicate a slight but not statistically significant 0.1 unit decrease in L*, a statistically significant increase in b* ( P = 0.049), and a statistically significant 1.0 unit decrease in ITA ( P = 0.04) between the winters of 2008 and 2011.…”
Section: Resultsmentioning
confidence: 99%
“…The sun-protected group included 40 women aged 35–65 years who were selected from our previous 2008 study 3,4. These volunteers were recalled to meet our secondary aim of identifying any changes in facial skin tone over a 3-year period.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Skin darkening with age has previously been described in various populations, for example, a Chinese group living in Chicago as reported by de Rigal et al, [7] However, such age-related changes were not observed in African-Americans, Caucasians, and Mexicans. A recent study on Chinese women living in China [8] showed progressive darkening of the complexion with advancing age. A more recent study conducted in eight Asian cities found that Asian skin is generally darker with age.…”
Section: Discussionmentioning
confidence: 98%